Canine lumbosacral fracture-luxation stabilised with the String of Pearls interlocking plate system or pins combined with polymethylmethacrylate : a biomechanical comparison - Coetzee, Gert L. (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2016.